[Group portrait], March 1916 (1916)
Right to left: Arthur Matthews, Helen Shippey, John Fitzgerald, Bessie Renetzky, Bernice Dempsey, Jack Leonard, Peggy Shippey, Jerry Fitzgerald, in front, Josie Renetzky, Jean Riley